Nitrogen allocation among leaves and roots mediates the interaction between plant life history trade-off and density dependence - Cheng, Junkang; Yu, Shixiao (Frontiers in Plant Science, 2025)
IntroductionCarbon, nitrogen and phosphorus, as the basic components of plants, determine plant growth and adaptation strategies, while there are certain differences in nutrient allocation among different plant organs. However, little is known about the manner in which resource allocation mediates the plant life history strategy.MethodsHere, we collected three census field survey datasets from the Heishiding 50-ha dynamic plot showing functional traits and nutrient allocation among leaves and roots (⍺nutrient) from 92 woody species to determine the relationship between nutrient allocation and the plant life history strategy.ResultsCarbon allocation ⍺carbon was mainly determined by intraspecific variation while nitrogen allocation ⍺nitrogen and phosphorus allocation ⍺phosphorus was determined by interspecific variation. Species allocating more nitrogen to leaves showed greater resource acquisition traits, while species allocating more nitrogen to roots showed greater resource conservation traits. We found a trade-off between the plant relative growth rate and conspecific density dependence; fast-growing species showed higher mortality with conspecific neighbors but tended to allocate more nitrogen to leaves rather than roots.DiscussionOur study revealed interspecific variation in nutrient allocation among leaves and roots as well as their relationship with functional traits and the plant life history strategy.